Level of Preparedness of the Barangay Official and Barangay Purok During Pandemic COVID-19 at 171 Bagumbong, Caloocan City: Vol.3, No.1C (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aims to determine the level of preparedness of the barangay officials and barangay purok during COVID-19 at 171 Bagumbong Caloocan City. Ten barangay officials and 20 barangay purok are the respondents. The researchers use purposive sampling to access a particular subset of people, as all survey participants are selected because they fit a particular profile. The study employed qualitative descriptive research design, frequency and percentage distribution, weighted mean, point Likert, and ranking to answer whether barangay officials and barangay purok are prepared during the COVID-19 pandemic. The study revealed that barangay officials and barangay purok are highly prepared effectiveness the law enforcers in maintaining peace and order and distribution of relief goods, safety guidelines, and health protocol at 171 Bagumbong Caloocan City; in addition, the problems encountered by people who are violating the curfew hours, limited transportation are the most serious at 171 Bagumbong Caloocan City. The study recommended that Barangay officials ensure that each protocol and regulation are based on the resolutions of the professionals to manage the risk and eliminate further escalation of the crisis. Barangay Purok 171 should work with barangay officials and other frontliners to maintain peace and order. Health practitioners and other frontline personnel should attend a seminar to gain knowledge in dealing with issues such as the COVID-19 pandemic. Future researchers will expand on this data and information to better understand the community's situation. This study will serve as a foundation for solving a crisis such as the COVID-19 pandemic. Researchers should contribute to improving strategies and techniques for the event of a crisis for the next generation.